Auditory attentional set-shifting and inhibition in children who stutter - Kurt Eggers; Eira Jansson-Verkasalo (American Speech-Language-Hearing Association, 2022)
Purpose: The purpose of this study was to investigate whether previously reported parental questionnaire-based differences in attentional shifting and inhibitory control (AS and IC; Eggers, De Nil, & Van den Bergh, 2010) would be supported by direct measurement of AS and IC using a computer task.
Method: Participants were 16 Finnish children who stutter (CWS; mean age = 7.06 years) and 16 Finnish children who do not stutter (mean age = 7.05 years). Participants were matched on age (±8 months) and gender. AS and IC were assessed by the auditory set-shifting task of the Amsterdam Neuropsychological Tasks (De Sonneville, 2009).
Results: No group differences were found for the speed of auditory AS or IC. However, CWS, as a group, scored significantly lower on the accuracy (error percentage) of auditory AS. In addition, CWS, compared with the children who do not stutter, showed a higher increase in error percentages under AS and IC conditions.
Conclusions: The findings on error percentages partly corroborate earlier questionnaire-based findings showing difficulties in CWS on AS and IC. Moreover, it also seems to imply that CWS are less able to slow down their responses to achieve higher accuracy rates.